\[\begin{equation} \begin{split} 23^2=&23 \cdot 23 \quad & \ldots ① \\ 23^2-23^2=&23 \cdot 23-23 \cdot 23 \quad & \ldots ② \\ (23+23)(23-23)=& 23(23-23) \quad & \ldots ③ \\ \require{cancel} (23+23)\cdot \cancel{0}=&\require{cancel}23\cdot \cancel{0} \quad & \ldots ④ \\ 23=&46 ⇒ 1=2 \quad & \ldots ⑤\end{split} \end{equation} \]

The above equations lead us to a conclusion that \( 1 = 2 \). Then which of these steps contains the flaw.

*Try more problems* **here.**

×

Problem Loading...

Note Loading...

Set Loading...